Analysis Of Marketing Innovation Using The Digital Marketing Canvas For UMKM Albaby Official - Muhammad Rayza Hemawan; Mira Nurfitriya; Nizza Nadya Rachmani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Innovation in a business is an important key to remaining competitive and improving the quality of products, services and marketing. So it can increase customer awareness and satisfaction and increase revenue. The aim of this research is to find out the description and formulation of Marketing Innovation using the Digital Marketing Canvas approach at Albaby Official MSMEs. The object of the research is an MSME that operates in the fashion sector, especially baby shoes. Located in Dramaga, Bogor Regency. Using a qualitative case study approach. This study focuses on understanding the problems faced by MSMEs regarding digital adoption and the innovations they implement. Using primary data through observation, semi-structured interviews with MSME owners and secondary data including MSME sales data. Alleged interim results : MSME Albaby Official is experiencing problems with products and marketing, the core problem is in marketing because MSME Albaby Official only uses the Shopee platform to market its products. It is hoped that by implementing marketing innovations in its business, MSME Albaby Official can increase brand awareness and increase revenue. The results of this research confirm that the application of the Digital Marketing Canvas has helped MSMEs in developing effective marketing strategies and adapting themselves to rapidly changing market dynamics.